Efficient Perovskite Hybrid Solar Cells via Ionomer Interfacial Engineering. (19th October 2015) - Wang, Kai; Liu, Chang; Yi, Chao; Chen, Long; Zhu, Jiahua; Weiss, R. A.; Gong, Xiong
Abstract : The surface of the solution‐processed methylammonium lead tri‐iodide (CH3 NH3 PbI3 ) perovskite layer in perovskite hybrid solar cells (pero‐HSCs) tends to become rough during operation, which inevitably leads to deterioration of the contact between the perovskite layer and the charge‐extraction layers. Moreover, the low electrical conductivity of the electron extraction layer (EEL) gives rises to low electron collection efficiency and severe charge carrier recombination, resulting in energy loss during the charge‐extraction and ‐transport processes, lowering the efficiency of pero‐HSCs. To circumvent these problems, we utilize a solution‐processed ultrathin layer of a ionomer, 4‐lithium styrenesulfonic acid/styrene copolymer (LiSPS), to re‐engineer the interface of CH3 NH3 PbI3 in planar heterojunction (PHJ) pero‐HSCs. As a result, PHJ pero‐HSCs are achieved with an increased photocurrent density of 20.90 mA cm −2, an enlarged fill factor of 77.80%, a corresponding enhanced power conversion efficiency of 13.83%, high reproducibility, and low photocurrent hysteresis. Further investigation into the optical and electrical properties and the thin‐film morphologies of CH3 NH3 PbI3 with and without LiSPS, and the photophysics of the pero‐HSCs with and without LiSPS are shown. These demonstrate that the high performance of the pero‐HSCs incorporated with LiSPS can be attributed to the reduction in both the charge carrier recombination and leakage current, as well as more efficient charge carrier collection, filling of the perforations in CH3 NH3 PbI3, and a higher electrical conductivity of the LiSPS thin layer. These results demonstrate that our method provides a simple way to boost the efficiency of pero‐HSCs. Abstract : An ultrathin layer of a highly electrical conductive ionomer, 4‐lithium styrenesulfonic acid/styrene copolymer (LiSPS), is employed to re‐engineer the interface between the perovskite active layer and the electron‐extraction layer in perovskite hybrid solar cells. This results in an enhanced power‐conversion efficiency of 13.83% with high reproducibility and low photocurrent hysteresis.